Comparative study of threadfin bream (Nemipterus japonicas) scale collagen extracted using pineapple waste juice and citric acid / Nurul Hasanah Abd Majid. - Abd Majid, Nurul Hasanah (2016)
Collagen was isolated from the scale of threadfin bream using 0.5 M citric acid and pineapple waste juice at the duration 12hrs at 4 °C. The collagen physiochemical characteristics were studied and compared. The collagen yield were about 2.93 to 52.83% (on a dry weight basis), depending on the extraction solution. Pineapple waste juice treated collagen were light yellow (L = 89.18, a* = -0.19, b* = 9.28) while collagen produced using 0.5 M citric acid were white (L = 96.00, a* = 0.22, b* = 0.99). Sensory evaluation on odor recognition study showed the collagen extracted with pineapple juice had pungent sour odor while collagen produced using 0.5 M citric acid had chemical odor. The SDS PAGE profile threadfin bream collagen were type I collagens and consist of two different chains, al and a2. Threadfin bream scale collagens extracted using 0.5 M citric acids were more viscous than those from pineapple waste juice extracted collagen. Collagen from pineapple waste juice can be used as potential alternative for the production of acid soluble collagen.